2004
DOI: 10.1093/humrep/deh123
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial progesterone and estrogen receptors and bleeding disturbances in depot medroxyprogesterone acetate users

Abstract: Endometrial PRAB, PRB, ERalpha and ERbeta expression in glands and stroma was not different between DMPA users who had frequent or prolonged bleeding and amenorrhoeic DMPA users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Factors unrelated to progesterone and oestrogen receptor expression may therefore be involved in causing bleeding disturbances 14 . Hickey et al suggested that the endometrial vascular changes observed after long-term progestinonly contraceptives may reflect biological differences between natural progesterone and synthetic progestins 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Factors unrelated to progesterone and oestrogen receptor expression may therefore be involved in causing bleeding disturbances 14 . Hickey et al suggested that the endometrial vascular changes observed after long-term progestinonly contraceptives may reflect biological differences between natural progesterone and synthetic progestins 15 .…”
Section: Discussionmentioning
confidence: 99%
“…ER however, is expressed at lower levels in the stroma and glands in Norplant users when compared with normal proliferative phase endometrium (Critchley et al 1993). Neither PR nor ER is altered in women using depot MPA experiencing frequent bleeding episodes when compared with women who experienced amenorrhea (Sereepapong et al 2004). However, in women using LNG-IUS, PR is suppressed (Critchley et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…However, when exposed to lower uterine concentrations of progestogens, such as Implanon or Norplant, PR is high (Critchley et al 1993, Macpherson et al 1999. ER does not appear to be altered in Implanon users nor women using depot medroxyprogesterone acetate (MPA; Sereepapong et al 2004), however, it is lower in endometrium from Norplant users when compared with normal proliferative phase endometrium (Critchley et al 1993). Progestogens induce changes in ER and PR expression, which are likely to be involved in the observed histological differences and bleeding problems associated with specific p-only contraceptives.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this is a primary or secondary event is unknown, but this information may be an important finding in attempting to characterize both the molecular etiology of implantation and the molecular pathophysiology of spontaneous abortion. Alterations in the ratio of PGR isoform expression likely cause disordered regulation of target genes, resulting in altered progestin action in the uterus [51]. Progesterone inhibits human endometrial cancer cell growth and invasiveness [52].…”
Section: Discussionmentioning
confidence: 99%